Fluid Dynamic Studies in Support of an Industrial Ebullated Bed Hydroprocessor - Pjontek, Dominic (Université d'Ottawa / University of Ottawa, 2014)
Commercial ebullated bed hydroprocessors, such as the LC-Finer, are used for the production of synthetic crude oil by upgrading bitumen extracted from the Alberta oil sands. The objective of this thesis was to investigate the impact of an increased vacuum distillation tower bottoms feed fraction on the reactor fluid dynamics (e.g., bed and freeboard phase holdups, bubble characteristics and local fluidization behaviour). Industrial conditions were simulated in a high pressure gas-liquid-solid fluidization system based on dimensional and geometric similitude. Considering important geometric characteristics and matching dimensionless groups, base-case conditions resulted in an ebullated bed of nitrogen, 0.5 wt.% aqueous ethanol, and aluminum cylinders (average lengths and diameters of 7.5 and 3.2 mm, respectively) operating at 6.5 MPa and a gas-to-liquid superficial velocity ratio of 0.78. The proposed scale-down method resulted in high gas holdup conditions similar to industrial measurements. The use of the Sauter mean diameter to account for particle size and shape at the simulation conditions was investigated by comparing glass spheres with diameters of 4 and 1.5 mm to aluminum cylinders with equivalent volume-to-surface area ratios. Local bubble characteristics, including gas holdups, bubble rise velocities, and chord lengths, were then investigated under various operating conditions using a monofibre optical probe. Overall fluid dynamics were studied when increasing the liquid viscosity and varying the gas and liquid superficial velocities due to their relevance for industrial ebullated bed hydroprocessors. Freeboard and bed region gas holdup relations were studied and correlations were developed for gas and solid holdups at the simulation conditions based on the dimensionless groups. Mesophase generation in hydroprocessors due to undesired secondary reactions was also considered for an increased vacuum residue feed fraction. Adding a dispersed immiscible liquid phase which preferentially wetted the particles was therefore experimentally studied at non-simulating conditions using nitrogen, biodiesel, glycerol and various particles, where fluidization behaviour and phase holdups were considerably affected due to particle clustering. A study on the impacts of particle size, shape and material demonstrated the influences of fluid and particle properties, specifically the relative surface energies and viscous forces, on agglomeration due to interparticle liquid bridging.
Keywords: Fluidization; Ebullated bed; Dynamic similitude; High pressure; Mesophase; Agglomeration